2020
DOI: 10.17116/oftalma2020136052163
|View full text |Cite
|
Sign up to set email alerts
|

Transcanalicular balloon dacryoplasty for the treatment of post-dacryocystorhinostomy recurrent stenoses

Abstract: РЕЗЮМЕ Цель исследования. Провести сравнительный анализ эффективности малоинвазивных вмешательств при облитерации устья слезных канальцев у пациентов после дакриоцисториностомии. Материал и методы. В исследование включен 121 пациент (127 случаев), из которых 61 человек (64 случая) был со стенозом устья слезных канальцев, 60 (63 случая)-с облитерац ией устья слезных канальцев. Стеноз и облитерация устья слезных канальцев явились следствием рецидива проведенной ранее (от 6 мес до 5 лет) эндоназальной эндоскопиче… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…When ostium closure occurs, clinical treatment methods are different. Some studies suggest that lacrimal probe can be used to probing the closed ostium, or YAG laser can be used to open the ostium and insert arti cial lacrimal stent at the same time, but the above treatment effects are not ideal [14][15]. It is also reported that rhinostomy ostium incision can be performed to reopen the closed ostium and its curative effect is not very impressive [16].…”
Section: Introductionmentioning
confidence: 99%
“…When ostium closure occurs, clinical treatment methods are different. Some studies suggest that lacrimal probe can be used to probing the closed ostium, or YAG laser can be used to open the ostium and insert arti cial lacrimal stent at the same time, but the above treatment effects are not ideal [14][15]. It is also reported that rhinostomy ostium incision can be performed to reopen the closed ostium and its curative effect is not very impressive [16].…”
Section: Introductionmentioning
confidence: 99%